2017
DOI: 10.1007/s10725-017-0312-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of humic acid molecular fractions on growth and development of soybean seedlings under salt stress

Abstract: In the present study, the influence of humic acid (HA) molecular fractions (HA < 30 kDa and HA > 30 kDa) on enhancing the tolerance of seedlings of soybean [Glycine max (L.) Merr.] Progres and Nawiko cultivars to salt stress (50 mM NaCl) was investigated. HA were extracted from mountain fen soil and then were separated into two molecular fractions by membrane filtration and characterized by diffusion coefficient (Dapp), electrolytic conductivity (κ) and electrophoretic mobility (Ue). The following biomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…These findings give insights into the beneficial effects of humic acid on Giza 179 plant growth under nonsaline and saline conditions. Similar growth-promoting effects of humic acid have been reported in other rice cultivars [26,27], soybean seedlings [28], and maize [29]. These findings are supported by the results of PCA analysis (Figure 4A) that revealed differences between humic acid-treated and non-treated rice plants growing in non-saline and saline conditions.…”
Section: Humic Acid Priming Improves Giza 179 Plant Growth Under Non-...supporting
confidence: 87%
“…These findings give insights into the beneficial effects of humic acid on Giza 179 plant growth under nonsaline and saline conditions. Similar growth-promoting effects of humic acid have been reported in other rice cultivars [26,27], soybean seedlings [28], and maize [29]. These findings are supported by the results of PCA analysis (Figure 4A) that revealed differences between humic acid-treated and non-treated rice plants growing in non-saline and saline conditions.…”
Section: Humic Acid Priming Improves Giza 179 Plant Growth Under Non-...supporting
confidence: 87%
“…In our study, the lowest grain yield was found in the L treatment among the soil amendment treatments, although the combined application of L and F could significantly improve the grain yield of winter wheat in a winter wheat–summer maize rotation. This is mainly due to the ability of L to provide a large amount of carbon and F to improve soil microbial activity (Matuszak‐Slamani et al, 2017). Thus, the combined treatments can improve soil nutrient availability and crop yield.…”
Section: Discussionmentioning
confidence: 99%
“…A wide array of bio-stimulant compounds has been utilized to mitigate the salinity-induced injury to crop growth, development, and productivity. Humic acid reduces the salinity stress and increases the yield of many crop plants (Jarošová et al, 2016;Matuszak-Slamani et al, 2017;Saidimoradi et al, 2019). It positively affects multiple indices of plant growth including root and shoot growth, leaf photosynthetic pigments, yield, and its related traits (Osman et al, 2017;El-Beltagi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%